To Compare the Outcome of Patients Who Are Receiving Remdesivir within 10 Days of Symptom Onset to those Receiving Remdesivir after 10 Days of Symptom Onset - H R, Avinash; N, Satyanarayana; S B, Vaibhav; P, Pratheek (International Journal of Innovative Research in Medical Science, 2021)
Background: A novel coronavirus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), was first identified in December 2019 as the cause of a respiratory illness designated Covid-19.Several therapeutic agents have been evaluated for the treatment of Covid-19, but no antiviral agents have yet been shown to be efficacious. Remdesivir (RDV) is the only antiviral drug registered currently for the treatment of COVID-19 after a few clinical trials with controversial results. The purpose of this study was to compare the outcome of patients who are receiving Remdesivir within 10 days of symptom onset to those receiving Remdesivir after 10 days of symptom onset. Objectives: To compare the outcome of patients who are receiving Remdesivir within 10 days of symptom onset to those receiving Remdesivir after 10 days of symptom onset. Materials and Methods: A retrospective study was conducted on 100 patients admitted to ESIC MC & PGIMSR MODEL HOSPITAL BENGALURU during the study period from July 2020 to December 2020. Data were collected from case files of patients presenting to the Department of General Medicine Triage and COVID Ward/ICU at ESIC Bangalore fulfilling the inclusion criteria. Results: In the study, the percentage of patients who were discharged were 93.2% in the patients who received Remdesivir within 10 days of onset of the symptoms and 75% in patients who received Remdesivir more than 10 days of onset of the symptoms. The death was significantly lower among those were received Remdesivir early (<10 days) i.e. 6.8%, while 25% among those who received the same treatment late (>10days). This observation is significant with a p-value of 0.039. Conclusion: The study concludes that there is a significant improvement in the outcome of the patients who have received Remdesivir within 10 days of onset of symptoms in comparison to those who have received Remdesivir after 10 days of onset of symptoms.